PROBLEMS IN THE IMPLEMENTATION OF CONTEXTUAL TEACHING AND LEARNING IN TEACHING ENGLISH AT ELEVENTH GRADE STUDENTS OF MAN KLATEN - Hidayati, Anni Nurul (MAGISTRA, 2017)
The objectives of the study are: (1) describing the implmentation of CTL in the process ofteaching and learning; (2) describing the teachersâ difficulties in implementing CTL; (3) describing the teachersâsolution to overcome the difficulties in implementing CTL.The research was conducted in XI Science of MAN Klaten. The research uses descriptive qualitatifmethod. The sources of the data are events, informants, and documents. The data are collected using naturalisticobservation, interview, and document analysis. The reaserch uses interactive model anlysis; (1) data reduction;(2) data display; (3) conclusin drawing and verivication in anlyzing the data.The results of the research are: (1) English teacher of MAN Klaten perceive that CTL is a teaching andlearning approach in which appropiates with the 2013 curriculum; (2) CTL has been implemented well in theteaching and learning process; (3) the problems faced by the teachers are the teacherâs difficulties in managingthe time, studentsâs low motivation because they know English is difficult, and studentsâ difficulties in masteringvocabularies.In conclusion, CTL has been implemented well in the teaching and learning process of English class atMAN Klaten. The reseracher suggests some solutions to overcome the problems in implementing CTL in theteaching and learning English, here are the solutions: (1) Preparing and planning the teaching process; (2)Approaching and motivating students intensively; (3) Using various teaching strategies; (4)Sharing with otherteachers; (5)Integrating the teaching materials in order to fulfill the objective of some productive subject matters;(6)Ask the students to make personal vocabulary notes in daily teaching-learning activity.Keywords: Contextual, Teaching, Learning